2000
DOI: 10.1093/emboj/19.17.4439
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of human muscleblind proteins to (CUG)n expansions associated with myotonic dystrophy

Abstract: Myotonic dystrophy (DM1) is an autosomal dominant neuromuscular disorder associated with a (CTG) n expansion in the 3¢-untranslated region of the DM1 protein kinase (DMPK) gene. To explain disease pathogenesis, the RNA dominance model proposes that the DM1 mutation produces a gain-of-function at the RNA level in which CUG repeats form RNA hairpins that sequester nuclear factors required for proper muscle development and maintenance. Here, we identify the triplet repeat expansion (EXP) RNAbinding proteins as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
874
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 826 publications
(922 citation statements)
references
References 39 publications
30
874
1
4
Order By: Relevance
“…12 In other dominant intronic repeat disorders, such as Myotonic Dystrophy (DM1), these foci have been shown to sequester RNA-binding proteins, which cause a range of deleterious changes in RNA processing. 34,35 We propose that all C9ORF72 HREM cases derive from a single common founder and are now the most common cause of familial and sporadic ALS in Western Europe. The GGGGCC repeat is highly polymorphic and particularly unstable in the context of a specific haplotype (r), but the massive pathogenic expansion may have arisen on just one occasion around 6300 years ago.…”
Section: Human_reference : Gcgcgctaggggccggggccggggcc---------------mentioning
confidence: 99%
“…12 In other dominant intronic repeat disorders, such as Myotonic Dystrophy (DM1), these foci have been shown to sequester RNA-binding proteins, which cause a range of deleterious changes in RNA processing. 34,35 We propose that all C9ORF72 HREM cases derive from a single common founder and are now the most common cause of familial and sporadic ALS in Western Europe. The GGGGCC repeat is highly polymorphic and particularly unstable in the context of a specific haplotype (r), but the massive pathogenic expansion may have arisen on just one occasion around 6300 years ago.…”
Section: Human_reference : Gcgcgctaggggccggggccggggcc---------------mentioning
confidence: 99%
“…[2][3][4] At the molecular levels, the DM1 phenotype is most likely caused by a complex molecular pathogenesis, including deficiency of myotonic dystrophy myotonin kinase (DMPK) protein, [5][6][7] haplo-insufficiency of a neighboring homeobox gene (particular the DM locus-associated homeodomain protein (DMAHP/Six 5 gene) 8 and the WD-repeat gene (DMWD) 9 and a trans-dominant misregulation of RNA homeostasis. [10][11][12][13][14][15][16] Recent experiments from transgenic mice, expressing an untranslated expanded CUG repeat under the control of the human skeletal actin promoter, showed that expanded CUG repeats are sufficient to generate DM1 muscle phenotype. 17 These data suggest that misregulation of RNA homeostasis may play a major role in DM1 muscle pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…12 In DM muscle, a downregulation of MBNL1 function and an upregulation of CELF1 function was shown. [15][16][17][18] For CELF1, multiple functions in RNA metabolism have been reported including regulation of alternative splicing, RNA stability and translational regulation of its RNA targets.…”
Section: Introductionmentioning
confidence: 96%
“…10 Both genetic types share a common pathomechanism: mutant mRNA transcripts containing CUG/CCUG expansions are retained in the nucleus and aggregate as nuclear foci. 11 RNA-binding proteins sequester in the nucleus, 12 resulting in mis-splicing of downstream effector genes (reviewed by Ranum and Cooper 13 ).…”
Section: Introductionmentioning
confidence: 99%